PENGARUH KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA PERAWAT DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Maisy Wulandari; Roesdi Rosnelly; Tyasiningsih Ezky (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted on nurses at Arifin Achmad Hospital, RiauProvince with the aim of analyzing the influence of leadership and workload onjob satisfaction and nurse performance. The population in this study were allnursing staff who served in 21 inpatient rooms at Arifin Achmad Hospital,amounting to 487 people. The data collection technique was done through aquestionnaire technique, the data in the form of primary data and secondary data.The analytical method used in this study is path analysis with the help of SPSS 21.The results of this study indicate that leadership has a significant positive effecton job satisfaction. And workload has a significant negative effect on jobsatisfaction. leadership and job satisfaction have a significant positive effect onnurse performance. The workload has a significant negative effect onperformance. Job satisfaction is able to mediate the influence of leadership andworkload on nurse performance. Keywords: Leadership, Workload, Job Satisfaction and Performance